1979
DOI: 10.1104/pp.64.6.930
|View full text |Cite
|
Sign up to set email alerts
|

Net Photosynthesis and Early Growth Trends of a Dominant White Oak (Quercus alba L.)

Abstract: ABSTRACrExamination of the relationship betwee photosnthesis an growth of a do I white oak (Quevcw alm L) tree hs shown that most greow processes were eer led or well aderway before the ests t of s t posve rates of net potosts Growth was intiated first In the root system (March 3), folowed by stem cambial grwth (March 26) and later by flower, kleaf an b grwth (April 10 The photosynthetic process of white oak has been investigated in several studies (3,9,14 in clay content with depth from a silty clay loam at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

1983
1983
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 14 publications
1
35
0
Order By: Relevance
“…The growth trends here described for this evergreen species are similar to those reported for a deciduous oak by Dougherty et al (1979), and it is likely that an equivalent below-ground dynamics occurs for Q. suber. Those authors observed that root and stem cambial growth were the first phenological events, ceasing by the time of leaf expansion, and resuming after leaves became a major exporter of photosynthate.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The growth trends here described for this evergreen species are similar to those reported for a deciduous oak by Dougherty et al (1979), and it is likely that an equivalent below-ground dynamics occurs for Q. suber. Those authors observed that root and stem cambial growth were the first phenological events, ceasing by the time of leaf expansion, and resuming after leaves became a major exporter of photosynthate.…”
Section: Discussionsupporting
confidence: 79%
“…The rapid leaf emergence, expansion, and thickening observed in this study suggest not only a protection strategy against desiccation and herbivory (Mooney et al 1974), but also an opportune investment while water availability and climatic conditions are still suitable for maximum photosynthetic production (Dougherty et al 1979;Oliveira et al 1992). According to McLaughlin and McConathy (1979), most of the carbon was probably incorporated into new leaves and shoots during this period.…”
Section: Discussionmentioning
confidence: 95%
“…On 7 May, the leaves were not fully enlarged, the assimilation rates of which were high. Others have noted that A in deciduous leaves approaches maximum values before leaves are fully expanded (Dougherty et al, 1979). The early development of photosynthetic capacity is especially advantageous for tree growth in a Mediterranean climate where the drought starts early.…”
Section: Seasonal Trends In Assimilation Ratementioning
confidence: 98%
“…To more accurately reflect the growth response of tree species to changing temperature, parameters dictating the heat tolerance curve and optimal photosynthetic temperature for each tree functional group were updated. Empirical data on at least one species from each functional group was used and more when available (Ledig et al 1977, Dougherty et al 1979, Epron 1997, Jull et al 1999, Nedlo et al 2009, Turnbull et al 2001, Warren and Dreyer 2006, Weston and Bauerle 2007.…”
Section: Changes To the Century Succession Extensionmentioning
confidence: 99%